KARAKTERISTIK FISIK BUBUR INSTAN TERSUBTITUSI TEPUNG PISANG TONGKA LANGIT - Priscillia Picauly; Gilian Tetelepta (AGRITEKNO: Jurnal Teknologi Pertanian, 2015)
Instant porridge is sereal-based food that can be combined with fruits so it will contain better nutrition. To improve the nutrition value of instant porridge then substitute of one kind of banana originally from Maluku is Tongka langit banana. A good quality of instant porridge has a high nutrition and a best physical property. This research aims to characterize of the physical properties instant porridge that are substituted by Tongka langit banana flour and the rice flour. The design that is applied is completely randomized design with four levels of treatment in comparing the substitution between Tongka langit banana flour and the rice flour as follow 20%, 40%, 60% and 80%. According to the result of this research, the physical characteristic of instant porridge that are substituted by Tongka langit banana flour are bulk density (0.84-0.89 g/mL), water absorption index (3.49-4.05%), and water solubility index (0.02-0.04%).